Investigation of Surface Roughness and Material Removal Rate (MRR) on Tool Steel Using Brass and Copper Electrode for Electrical Discharge Grinding (EDG) Process - Helmi, M. Hafiz; Azuddin, M.; Abdullah, W. (International Journal of Integrated Engineering, 2009)
This paper presents the investigation on surface roughness and material removal rate (MRR) of tool steel machined with brass and copper electrode for Electrical Discharge Grinding (EDG) process. The machining parameter include pulse ON time, pulse OFF time, peak current and capacitance. Analysis of variance (ANOVA) with Taguchi method is used to investigate the significant effect on the performance characteristic and the optimal cutting parameters of EDG. The result shows that, the surface roughness value when using of both tool materials are mostly influenced by pulse ON time and peak current. The capacitance parameter in both experiments was not giving any significant effect. The significant factors for the material removal rate due to the machining parameter are peak current parameter and ON time parameter but it also can increase the machining time